Resistencia Antibiótica en Gestantes con Infección Urinaria. Hospital Provincial General Docente Riobamba 2017-2018 - Ricardo Alejandro Tenorio Suárez (2019)
The objective of this research project was to determine antibiotic resistance in urinary tract infections in pregnant women treated in the emergency service of the Provincial General Teaching Hospital of Riobamba. August 2017-July 2018, since bacteria are able to acquire resistance based on their genetic variability. New resistance mechanisms can be achieved with the transformation or through the transfer of genetic material between bacterial cells of related or dissimilar species. Methodologically it had a non-experimental design since the study variables were not manipulated, because of the type it was transversal and descriptive, the population was 232 pregnant patients of the Provincial General Teaching Hospital of Riobamba, the sample was 100 patients, the technique was a statistical program , the instrument was the Whonet Software, through which data was obtained, to be able to conclude that there is an end to drugs that have different levels of antibiotic resistance, the Escherichiacoli bacteria is 100% resistant to Ampicillin , 55.3% Trimethoprim / Sulfamethoxazole and Amoxicillin / Clavulanic acid, Doripenem, Imipenem, Amicacin, Erythromycin are sensitive with 100%, while the microorganism Proteusmirabilis with 77.8% is resistant to Nitrofurantoin, 55.6 % Trimethoprim / Sulfamethoxazole, 50% Ampicillin and Cefuroxime, Ceftazidime, Ceftriaxone, Cefepime, Ertapenem, Meropenem, Amicacin, Norfloxacin, etc. n sensitive with 100%, being those who have affected urinary tract infections in pregnant women.